THE TRANSITION TOWARDS A MULTI-CURRENCY WORLD ORDER - Stanojević, Nataša (Economic Outlook, 2025)
The article examines the ongoing global shift from the dominance of the US dollar in international transactions towards a multi-currency trade and financial system. The analysis identifies four key dimensions of this transformation: the decline of dollar hegemony, the growing use of alternative currencies in energy trade, the diversification of currencies in international payments, and the development of stand-alone payment infrastructures, such as SPFS, CIPS and SFMS, which facilitate a move away from SWIFT and the dollar-centred architecture. Taken together, these elements reflect a strategic rethinking of monetary power in an increasingly fragmented geopolitical environment. The article focuses on the case study of Russia, which has implemented the most comprehensive de-dollarisation strategy among major economies. Since 2022, Russia has significantly reduced the use of the dollar and euro in its foreign trade, replacing them with the rouble, yuan and other partner-country currencies. Bilateral agreements, institutional coordination within the Eurasian Economic Union and BRICS, and region-specific trade data are used to illustrate the scope and implications of this currency transition. While the Russian case is the most prominent due to data availability, similar tendencies in China, India and the Gulf Arab states are also examined. The study employs a qualitative methodology supported by descriptive statistics, drawing on official trade and payments data, summit communiqués and secondary sources to trace currency use and institutional developments. The findings suggest that, although dollar dominance remains structurally entrenched, a multipolar monetary order based on regional financial blocs and alternative transaction channels is gradually emerging. This new system is expected to gain resilience through the convergence of monetary, trade and technological strategies.